Peningkatan Derajat Self-Esteem Istri Korban Kekerasan dalam Rumah Tangga melalui Penerapan Cognitive Behavior Therapy di Kota Bandung - Putri Aprilianti; O. Irene Prameswari Edwina; Lie Fun Fun (Humanitas (Jurnal Psikologi), 2019)
This study aims to see an increase in the degree of Self-esteem to all wives who became victim of domestic violence in Bandung after being given Cognitive Behavior Therapy. The measuring equipment used is Self-esteem questionnaire based on Self-esteem Theory of Murk as a dependent variable that consists of 32 items. Validity Test used to measured Self-esteem was done by using Expert Validity method. The data obtained in this study will be analyzed qualitatively. The results showed there is an increase in Self-esteem scores on domestic violence victims after the therapy. The theoretical suggestion for further research is to add more varied ways of assigning tasks to the client, therefore made the therapy sessions more interesting and the clients more motivated to be actively involved in the completion to the assigned tasks. Suggestions for Psychologists who will handle cases of domestic violence, could utilize Cognitive Behavior Therapy to increase Self-esteem on domestic violence victims. Keywords: self-esteem, victim of domestic violence, and cognitive behavior therapy